IMF Research Perspective : Fall 21/Winter 22. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2022)
This issue of the IMF Research Perspective looks at the inter-connectedness of the world economic system and how diverse shocks can affect global supply chains. The articles in this issue track the way COVID-19 triggered disruptions in the supply chain and explains why trade networks are so difficult to disentangle. However, the pandemic is not the only event affecting global supply chains; cross-border spillovers of technology wars and natural disasters are other factors to consider. The overarching message from these articles is clear: there is a need for international cooperation to deal with the consequences of these shocks-whether it is ending the COVID-19 pandemic or mitigating climate change.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Climate; International Agreements and Observance; International Organizations; Investment Decisions; Portfolio Choice